ARTICLE TITLE THE RELEVANCE OF "JATI KASILIH KU JUNTI" PHILOSOPHY IN LOCAL CURRICULUM FOR DEVELOPING SUNDANESE IDENTITY AND "SOMEAH" CHARACTER IN ELEMENTARY SCHOOLS: A SYSTEMATIC LITERATURE REVIEW - Iman Budiman; Yusuf Tri Herlambang; Yunus Abidin (SOSIOEDUKASI, 2026)
This study investigates the significance of the "Jati Kasilih Ku Junti" philosophy in the local curriculum aimed at enhancing elementary school students' identity and character through a systematic literature review. The impact of globalization has led to a decline in Sundanese local wisdom values, particularly the someah character, which is a core component of Sundanese identity. This study employs a systematic literature review (SLR) methodology, analyzing 40 articles obtained from SINTA 3, SINTA 2, and SCOPUS databases, covering the years 2015 to 2025. Inclusion criteria encompass articles addressing character education based on local wisdom, Sundanese philosophical perspectives, and local curriculum implementation within the elementary education framework. Data analysis was conducted using content analysis and thematic analysis methodology. The findings indicate that the "Jati Kasilih Ku Junti" philosophy is highly relevant in promoting the development of someah character across three dimensions: cognitive (understanding values), affective (appreciating values), and psychomotor (practical application of values). Implementation of local curriculum informed by Sundanese wisdom can be realized through ethnopedagogical approaches, integration into local subjects, and Pancasila Student Profile Strengthening Project initiatives. Development strategies include contextual learning, integration of someah values into school culture, and outreach efforts directed at educators. This research contributes theoretically to the evolution of character education models rooted in Sundanese ethnopedagogy, while also serving as a practical reference for education practitioners in formulating effective local curricula aimed at preserving Sundanese cultural values in the elementary education context.